Peningkatan Pengetahuan Kelompok Ibu Hamil dalam Persiapan Persalinan di Masa Pandemi Covid-19 - Prastiwi, Ratih Sakti; Maulida, Iroma; Risqi, Intan Cristy Mayasari (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The increase in Covid-19 cases in Indonesia causes an increase in anxiety in pregnant women facing childbirth. In addition, several activities to educate pregnant women were postponed to reduce interactions to help reduce the spread of COVID-9 to pregnant women. Therefore, it is necessary to provide alternative health education for pregnant women to provide accurate and correct information. The provision of health education was carried out through a WhatsApp group by providing material in preparation for childbirth and preventing the transmission of covid-19. This activity involves ten pregnant women members of a pregnancy class, assisted by the Sumur Panggang Health Center. Health education was given through the interactive lecture method. All active participants in the activity were shown from the questions asked during the activity. This activity was following the target of the activity, namely pregnant women. This activity is beneficial in understanding pregnant women to prepare for childbirth, both from screening before the estimated birth, selecting the proper health facilities with the condition of pregnant women, and preventing transmission to babies and mothers.